(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2021)
Micro-electrical discharge machining (µEDM) has been proved to produce high surface quality results in Si machining. In previous studies, the researchers reported the Si machining using the µEDM with several strategies such as plating, doping and temporary coating process to be machined by the µEDM. This paper reports a numerical simulation of MRR performance results using COMSOL Multiphysics. The effects of the machining temperature in Si machining using heat-assisted µEDM on achieving the optimum MRR results is studied. The simulation results showed the highest MRR is 1.48666 × 10-5 mm3/seconds achieved at 250 °C.